The sacralization of the medical act. Ethical and professional values between medicine and pharmacy, Colombia, 1894-1914 - Márquez Valderrama, Jorge; Estrada Orrego, Victoria (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In Colombia, the history of professionalisation is a little explored issue. The social history of the sciences and the sociology of the professions constitute a basis from which to examine it. This article poses two questions as a starting point:  What are the relationships and confrontations between the medical profession and its related fields and how have they operated in the historical process of the professionalisation of medicine? How has the ethical discourse been manifested and how has it influenced this process? In order to illustrate the legitimisation of the monopoly of the practice of medicine in Colombia, a corpus of speeches and debates on its professionalization was established, with an emphasis on statements regarding ethics as a defence of the profession. Those discourses were published in the main medical and pharmacy journals of the country, between 1894 and 1914. The corpus shows that the medical arguments in favour of a monopoly on the practice of medicine, in addition to being scientific and economic, are political and ethical. They include argumentation in which are combined reflections on the moral qualities of doctors, as well as their legitimacy in the administration of the truth and the necessity to exert power in the delimitation of the profession.